A Longitudinal Echocardiographic Analysis of Patients Treated Using the Repositionable and Fully Retrievable Lotus Valve: A Sub-Analysis of the RESPOND Study. Issue 1 (2nd January 2020) - Soliman, Osama; Chang, Chun-Chin; Wöhrle, Jochen; Hildick-Smith, David; Bleiziffer, Sabine; Blackman, Daniel J.; Abdel-Wahab, Mohamed; Modine, Thomas; Nersesov, Andrey; Allocco, Dominic J.; Meredith, Ian T.; Falk, Volkmar; et al.
ABSTRACT: Background: The Lotus aortic valve system is a transcatheter heart valve (THV) designed with a seal to minimize paravalvular leak (PVL). We evaluated hemodynamic performance, PVL and ventricular function up to 1-year after transcatheter aortic valve replacement (TAVR) using the Lotus THV in patients with severe aortic stenosis. Methods: RESPOND was a prospective, single-arm, multicenter registry evaluating outcomes after Lotus TAVR in routine clinical practice. Core Laboratory adjudicated echocardiograms at baseline, discharge and 1-year were analyzed in a subgroup (N = 550) of patients with paired transthoracic echocardiography (TTE) at the 3 time points. Results: Mean effective aortic valve orifice area (EOA) in cm 2 increased from 0.74 ± 0.25 at baseline to 1.83 ± 0.46 at discharge and to 1.78 ± 0.45 at 1-year. Mean transvalvular gradient in mmHg was reduced from 38.7 ± 15.2 at baseline to 10.9 ± 4.2 at discharge and to 10.8 ± 5.1 at 1-year. VARC-2 hemodynamic success was achieved in 92% and 95% of patients at discharge and 1-year, respectively. Mild or more PVL was seen in 7.3% and 5.5% and moderate or more PVL was seen in 0.6% and 0.4% of the patients at discharge and 1-year, respectively. Stroke volume index (mL/m 2 ) increased from 35 ± 10 at baseline to 40 ± 11 at discharge and to 41 ± 11 at 1-year ( p < 0.001). Conclusions: This RESPOND sub-study demonstrates persistently favorable hemodynamic performance and a low rate of PVL in unselected patients through 1-year in the largest Lotus-treated population to date. (Re positionable Lotus Valve S ystem–Po st Market Evaluation of Real World Clinical Outcomes [RESPOND]; NCT02031302).